Knowing Groundlessness: An Enactive Approach to a Shift From Cognition to Non-Dual Awareness - Meling, Daniel (Frontiers in Psychology, 2021)
The enactive approach has become an influential paradigm in cognitive science. One of its most important claims is that cognition is sense-making: to cognize is to enact a world of meaning. Thus, a world is not pregiven but enacted through sense-making. Most importantly, sense-making is not a fixed process or thing. It does not have substantial existence. Instead, it is groundless: it springs from a dynamic of relations, without substantial ground. Thereby, as all cognition is groundless, this groundlessness is considered the central underlying principle of cognition. This article takes that key concept of the enactive approach and argues that it is not only a theoretical statement. Rather, groundlessness is directly accessible in lived experience. The two guiding questions of this article concern that lived experience of groundlessness: (1) What is it to know groundlessness? (2) How can one know groundlessness? Accordingly, it elaborates (1) how this knowing of groundlessness fits into the theoretical framework of the enactive approach. Also, it describes (2) how it can be directly experienced when certain requirements are met. In an additional reflexive analysis, the context-dependency and observer-relativity of those statements themselves is highlighted. Through those steps, this article exhibits the importance of knowing groundlessness for a cognitive science discourse: this underlying groundlessness is not only the “ground" of cognition, but it also can be investigated empirically through lived experience. However, it requires a methodology that is radically different from classical cognitive science. This article ends with envisioning a future praxis of cognitive science which enables researchers to investigate not only theoretically but empirically the “foundationless foundation” of cognition: groundlessness.